2019
DOI: 10.1155/2019/6458302
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Isolated Primary Pleural Neurofibroma in a 39-Year-Old Woman

Abstract: Primary benign neurogenic neoplasms of the pleura are exceedingly rare. Neurofibromas rarely involve the pleura. A review of the literarture reveals only a single reported case of isolated pleural neurofibroma. Herein the authors describe another case of isolated primary pleural neurofibroma. A 39-year-old nonsmoker woman presented to the emergency room with complaints of progressively worsening chest pain of one month duration. A computed tomography of the chest revealed a crescent shaped, pleural based mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Langman et al [ 5 ] reported two cases of primary localized pleural neurofibroma out of which one was a known case of neurofibromatosis type I. Krishnamurthy et al [ 6 ], reported another case of isolated pleural neurofibroma in a 39-year-old female who presented with worsening chest pain. Another case of a 31-year-old male with pleural neurofibroma was reported by Gupta et al [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Langman et al [ 5 ] reported two cases of primary localized pleural neurofibroma out of which one was a known case of neurofibromatosis type I. Krishnamurthy et al [ 6 ], reported another case of isolated pleural neurofibroma in a 39-year-old female who presented with worsening chest pain. Another case of a 31-year-old male with pleural neurofibroma was reported by Gupta et al [ 7 ].…”
Section: Discussionmentioning
confidence: 99%